Import tax as a determining factor in the consumer's purchase decision within electronic commerce - García Alay, Richard; Bermúdez Gallegos, Christian; Murillo Delgado, Paul (Revista Universidad de Guayaquil, 2019)
Electronic commerce in Ecuador maintains sustained growth in the last two decades thanks to the advances of ICTs. However, consumer behavior may be affected by the imposition of tax rates on transactions carried out. The purpose of this study is to determine the effect of an import tax rate on the online consumer's purchasing decision. For this, a quantitative methodology was considered, starting from a conceptual model and contrasting with the data taken from a random sample of 380 people who consume within electronic commerce. With a descriptive scope, the consumer profile was determined, and applying correlational analysis the strength of the relationship between the study variables was observed. The results show that online consumers are more inclined to buy clothes and footwear, and the female gender is more affected by the imposition of import taxes on their transactions.
Keywords: Import tax; consumer’s behavior; e-consumers